Das urnas para as urnas : o papel do juiz de paz nas eleições do fim do Império (1871-1889) - Souza, Alexandre de Oliveira Bazilio de (2012)
During its last years, the Brazilian Empire went through an intense process of change, as a result of the political turnaround that took place at the end of the 1860 s. In legislative terms, this scenario was characterized by the passing of several statutes that translated the new status quo, such as the Judiciary Reform in 1871. The imperial tradition of changing electoral law also accelerated during this time, when a set of electoral proposals were put forward. Among the authorities that mostly suffered the impact of the reforms were the justices of the peace, who were constantly accused of interfering in the elections. In fact, the Brazilian imperial justices of the peace were a source of great controversy among his contemporaries, chiefly because of his twofold link with suffrage: they were elected magistrates who, since 1830, functioned as the main administrators of the elections. On this dissertation, I discuss how Brazilian politicians debated the new role of the justice of the peace in the elections during this period and, conducting a case study on Espírito Santo, I show who the justices of the peace in this province were and how they performed their electoral duties.